2002
DOI: 10.1038/sj.bjc.6600299
|View full text |Cite
|
Sign up to set email alerts
|

Influence of epidermal growth factor receptor (EGFR), p53 and intrinsic MAP kinase pathway status of tumour cells on the antiproliferative effect of ZD1839 (‘Iressa’)

Abstract: ZD1839 ('Iressa') is an orally active, selective epidermal growth factor receptor -tyrosine kinase inhibitor (EGFR -TKI), which blocks signal transduction pathways implicated in proliferation and survival of cancer cells, and other host-dependent processes promoting cancer growth. Permanent downstream activation of the mitogen-activated protein kinase pathway can theoretically bypass the upstream block of epidermal growth factor receptor-dependent mitogen-activated protein kinase activation at the epidermal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(86 citation statements)
references
References 25 publications
(30 reference statements)
8
77
0
1
Order By: Relevance
“…EGFR expression was found to be higher in the radiosensitive S40b cell line (21.5 fmol mg À1 of protein) compared to the radioresistant MGH-U1 line (16.7 fmol mg À1 of protein), although this does not represent particularly high expression. Previous studies demonstrating an inverse correlation between the IC 50 of ZD1839 and EGFR expression are in agreement with our findings (Magne et al, 2002). However, other studies have suggested that the effects of ZD1839 on EGFR are not simply related to EGFR expression alone and may involve a complex interaction of heterodimerisation of ErbB-1 (EGFR) with other glycoprotein receptors in the subfamily such as ErbB-2 or ErbB-3 (Normanno et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…EGFR expression was found to be higher in the radiosensitive S40b cell line (21.5 fmol mg À1 of protein) compared to the radioresistant MGH-U1 line (16.7 fmol mg À1 of protein), although this does not represent particularly high expression. Previous studies demonstrating an inverse correlation between the IC 50 of ZD1839 and EGFR expression are in agreement with our findings (Magne et al, 2002). However, other studies have suggested that the effects of ZD1839 on EGFR are not simply related to EGFR expression alone and may involve a complex interaction of heterodimerisation of ErbB-1 (EGFR) with other glycoprotein receptors in the subfamily such as ErbB-2 or ErbB-3 (Normanno et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…ZD1839 has been shown to have growth inhibitory effects across a wide variety of cell types. The IC 50 for ZD1839 has been reported to be relatively cell line specific with values ranging from 0.15 to 31 mM (Ciardiello et al, 2001a;Magne et al, 2002). In our study, ZD1839 was found to have little effect on the growth characteristics of both cell lines as a single agent when studied at the doses previously reported to have significant growth inhibitory effects (Ciardiello et al, 2000).…”
Section: Discussionsupporting
confidence: 44%
“…p70S6 kinase inactivates the pro-apoptotic factor BAD; mTOR inhibitors or paclitaxel may promote apoptosis by preventing this inactivation. Consistent with these mechanisms, it has been shown that breast cancer cells resistant to the growth inhibiting effects of rapamycin are also resistant to its chemosensitising effects (Mondesire et al, 2004), and sequence-dependent enhancement of paclitaxel cytotoxicity has also been seen with gefitinib and trastuzumab, agents that like mTOR inhibitors inhibit growth factor signal transduction (Lee et al, 2002;Magné et al, 2002). However, in another study with cervical cancer cells, treatment with rapamycin preceding paclitaxel produced the more favourable result (Faried et al, 2006), suggesting that sequence dependency may be influenced by different mechanisms in other types of cancer.…”
Section: Discussionmentioning
confidence: 75%
“…CAL33 cells carry a p53 mutation (codon 175: CGC-CAC) and exhibit high EGFR expression (34 000 fmol mg À1 protein). CAL33 has no intrinsic mitogen-activated protein (MAP) kinase activity or k-ras mutation (Magné et al, 2002b).…”
Section: Drug Administration Schedulementioning
confidence: 99%